Appropriateness of peripheral parenteral nutrition use in adult patients at an academic medical center. (February 2018) - Sugrue, David; Jarrell, Andrew S.; Kruer, Rachel; Davis, Stephanie; Johnson, Dachelle; Tsui, Evelyn; Snyder, Sukyee; Crow, Jessica
Summary: Background & aims: Current evidence and guidelines identify patient populations who may benefit from parenteral nutrition. Peripheral parenteral nutrition (PPN) may be indicated for a subset of patients; however, PPN therapy carries a risk of associated adverse effects. The purpose of this project was to assess appropriateness of current PPN prescribing practices at an academic medical center to determine whether additional guidance and oversight may be beneficial. Methods: Adult patients admitted from August 1, 2015 to November 30, 2015 with at least one order of PPN administered were included. PPN use was evaluated for appropriateness using definitions derived from clinical practice guidelines and standard of practice. Adverse events, including phlebitis and bacteremia, were also examined. Results: Of the 159 patients included, 51 (32.1%) received appropriate PPN therapy, in which all four criteria for appropriateness were met. In regards to the criteria for appropriateness, 128 (80.5%) had an appropriate indication, 85 (53.5%) had appropriate time to PPN initiation, 157 (98.7%) had an appropriate duration of therapy, and 112 (70.4%) achieved an appropriate percentage of goal daily calories. In terms of complications associated with PPN therapy, 69 (43.4%) patients had documented phlebitis and bacteremia occurred in 5 (3.1%) of the patients. Conclusion: During the study period, PPN was appropriately utilized in only one-third of patients and phlebitis occurred in almost half of all patients. Restrictions on PPN prescribing may allow nutrition support clinicians to prospectively evaluate patients to optimize nutrition therapy and minimize the incidence of inappropriate PPN use.